Implementation of self-directed learning in enhancing skills dedicated to the community college teaching staff - M M Mohamad, M M Mohamad; A Ahmad, A Ahmad; M H Yee1, M H Yee1; T K Tee, T K Tee; A N Mohd Nasir, A N Mohd Nasir (2021)
Self-directed learning is a type used in the teaching force that requires high knowledge during the teaching and learning process. Self-learning requires educators to constantly improve their skills to prepare before teaching and learning. The purpose of this study is to learn self-study in Community College students. This study utilized a survey method which employed 169 Community College lecturers in Johor using questionnaire form. Overall, the results show a high percentage of strategies for drunkenness and self-directed learning. Therefore, this study found that there are several strategies for self-directed learning implemented by Johor Community College. These strategies have the advantage and potential in enhancing the existing skills of the teaching staff. Next, the highest implementation is carried out in open discussion. Open discussion can generate new ideas in the teaching force. Therefore, this information can assist lecturers in learning self-directed learning for their students.